Real Wages and the Cycle: The View from the Frequency Domain - Robert A. Hart; James R. Malley; Ulrich Woitek (Institute for the Study of Labor (IZA), 2001)
In the time domain, the observed cyclical behavior of the real wage hides a range of economic influences that give rise to cycles of differing lengths and amplitudes. This may serve to produce a distorted picture of wage cyclicality. Here, we employ frequency domain methods that allow us decompose wages into cyclical components and to assess the relative contribution of each component. These are discussed in relation to wages alone (the univariate case) and to wages in relation to production or employment-based measures of the cycle (multivariate). In the multivariate dimension, we derive methods for determining whether (i) wage and business cycles cohere (ii) lead-lag or contemporaneous relationships exist and (iii) the degree of coherency between wage and business cycles is time dependent. We establish that real wages are strongly procyclical and that the business cycle is the dominant associated influence.
Keywords: J31; E32; 330; Frequency domain; univariate case; multivariate case; phase shift; real wage cycles; Reallohn; Konjunktur; Multivariate Analyse; Dekompositionsverfahren; Schätzung; USA